2019
DOI: 10.18823/asiatefl.2019.16.2.6.531
|View full text |Cite
|
Sign up to set email alerts
|

Online Collaborative Writing Technique Using Wiki : How Effective is It to Enhance Learners’ Essay Writing?

Abstract: This paper focuses on the use of Wiki in enhancing learners' skills in writing argumentative essays. This paper describes the implementation of the online collaborative writing technique (OCWT) through Wiki activities and aims at analyzing the effectiveness of the OCWT to enhance the learners' argumentative essay writing. This study applied a descriptive method, involving a group of 29 students from the English Education Study Program at Universitas Terbuka (UT), Indonesia. In order to find out the effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
5
17
0
Order By: Relevance
“…Consistent with previous literature (Andrew, 2019;Ardiasih, Emzir, & Rasyid, 2019), the results also showed that the learners had positive attitudes toward online TBLT practices. Most learners were interested and motivated to learn writing with a Google Classroom tool.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous literature (Andrew, 2019;Ardiasih, Emzir, & Rasyid, 2019), the results also showed that the learners had positive attitudes toward online TBLT practices. Most learners were interested and motivated to learn writing with a Google Classroom tool.…”
Section: Discussionsupporting
confidence: 90%
“…The present study presents a pedagogical method based on CW for language acquisition, while promoting new and innovative pedagogical actions in the acquisition of the written expression [39] among students enrolled in the second year of non-compulsory secondary education (hereinafter, NCSE). Furthermore, it is intended to promote the development of further studies regarding this writing method [40][41][42][43][44], by following the same methodological process developed in other studies [57,58].…”
Section: Rationale and Objectives Of The Studymentioning
confidence: 99%
“…In the last decades, CW has been widely used in the field of English and all other foreign language learning. Moreover, it has been developed through diverse means [40], upon which the technological method stands out [41,42]. The proliferation of this method is due the potential benefits of acquiring a second language [43].…”
Section: Introductionmentioning
confidence: 99%
“…The first trend is the integration of specific online platform/method/technique in OCW (Ardiasih et al, 2019;Cho & Lim, 2017;Katz & Thoren, 2014;. Those studies showed a positive effect of integrating a specific online platform/method/technique in OCW.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stoddart et al (2013) further suggest that other researchers explore facilitation knowledge and practices in wiki-based collaborative writing of various academic domains and professional disciplines. Ardiasih et al (2019) studied Wiki's usage in writing argumentative essays to improve learners' skills. The study focuses on applying the OCW by Wiki practices and the reliability of OCW to improve the students' argumentative essays.…”
mentioning
confidence: 99%